2020
DOI: 10.1158/0008-5472.can-20-0069
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Density and Distribution of Tumor-Associated Macrophages Predict Survival in Non–Small Cell Lung Carcinoma

Abstract: The respective antitumoral and protumoral roles of M1 and M2 tumor-associated macrophages (TAM) typify the complexity of macrophage function in cancer. In lung cancer, density and topology of distinct TAM phenotypes at the tumor center (TC) versus the invasive margin (IM) are largely unknown. Here, we investigated TAM subtype density and distribution between TC and IM in human lung cancer and TAM associations with overall survival. Macrophages isolated from adjacent nontumor tissue (NM), the TC (TC-TAM), and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(123 citation statements)
references
References 44 publications
(61 reference statements)
8
114
1
Order By: Relevance
“…Interestingly, we find genes with opposite regulation in tumor epithelium and tumor stroma, which compartment-specific regulation would have not been found with bulk data: genes up-regulated in tumor stroma and down-regulated in tumor epithelium are enriched for cytokine secretion and Toll-like receptor 2 signaling, suggesting that the microenvironment produces different sets of cytokines than the tumor itself, possibly reflecting different chemoattraction and hence different immune cell proportions depending on tumor proximity. Indeed, immune cells' distribution has been found to be of clinical relevance in cancer [121][122][123].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we find genes with opposite regulation in tumor epithelium and tumor stroma, which compartment-specific regulation would have not been found with bulk data: genes up-regulated in tumor stroma and down-regulated in tumor epithelium are enriched for cytokine secretion and Toll-like receptor 2 signaling, suggesting that the microenvironment produces different sets of cytokines than the tumor itself, possibly reflecting different chemoattraction and hence different immune cell proportions depending on tumor proximity. Indeed, immune cells' distribution has been found to be of clinical relevance in cancer [121][122][123].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the number of TAMs generally shortens survival and increases the grade and stage of cancer. Specifically, they have been reported in gastric cancer, breast cancer, prostate cancer, classical Hodgkin's lymphoma, kidney cancer, nasopharyngeal cancer, and glioma [44][45][46][47][48][49][50][51][52]. CCL2-induced chemokine cascade promotes breast cancer metastasis by enhancing retention of TAMs [53].…”
Section: The Effects Of Ccl2 On Cancer Cell Via Tumor Microenvironmentmentioning
confidence: 99%
“…As it was shown that AMs were not significant contributors of TAM population in lung cancer (Loyher et al, 2018), we can hypothesize that TAMs actually originate exclusively from adult monocytes, with a varying time of residency within the tissue. In patients suffering from non-small cell lung carcinoma (NSCLC), another recent study highlighted a spatial heterogeneity between TAMs located in the tumor core and TAMs located at invasive margin (Zheng et al, 2020). Indeed, pro-tumoral TAMs were marked especially at the tumor-invasive margin.…”
Section: Macrophages and Lung Cancermentioning
confidence: 99%
“…Moreover, pro-tumoral TAMs were in closer contact to tumor cells as compared to the antitumoral ones. Finally, at the invasive margin, higher proximity of tumor cells to pro-tumoral TAMs and lower proximity to antitumoral TAMs were associated with poor survival (Zheng et al, 2020). Finally, another recent study of human and mouse NSCLC identified a new population of mature dendritic cells enriched in immuno-regulatory molecules (mregDCs) that limit antitumor immunity (Maier et al, 2020).…”
Section: Macrophages and Lung Cancermentioning
confidence: 99%